The correlation between low-carbon economy and energy technology innovation in the Yangtze River Delta region under spatial econometric methods - Zhang, Shengdi; Wang, Jiachen (Frontiers in Environmental Science, 2025)
IntroductionThe long‐term high carbon economic model, while driving economic growth, has also led to climate issues. Faced with this challenge, reducing carbon emissions and advocating low‐carbon economic development have become the focus of international attention. Although the Yangtze River Delta region holds an important position in economic and technological innovation, its carbon emissions are still continuously increasing. MethodsTo explore the mutual influence between low‐carbon economy and energy technology innovation, this study took the Yangtze River Delta region as the research object, collected data from the region from 2010 to 2022, and analyzed and explored the correlation between the two. Then, using spatial econometric methods, a spatial model was constructed to explore the spatial effects between the two in depth.ResultsResearch data showed that, taking adjacency matrix as an example, when the level of energy technology innovation increased by 1%, the low‐carbon economic development level in the Yangtze River Delta region would increase by 21.15%. In terms of geographical distance matrix, when the level of energy technology innovation increased by 1%, the low‐carbon economic development level in the Yangtze River Delta region would also increase by 19.95%. The energy technology innovation in the Yangtze River Delta was positively correlated with the development of low‐carbon economy, with energy innovation technology mainly improving the low‐carbon economic level of the Yangtze River Delta region through carbon reduction and decarbonization. In addition, the interaction between energy technology innovation and the environment also shows a significant spatial spillover effect on the development of low‐carbon economy.DiscussionIn summary, the empirical results of this study indicate that the Yangtze River Delta region should prioritize the following measures to enhance its energy technology innovation and promote low-carbon development: The first is to encourage enterprises and scientific research institutions to increase investment in low‐carbon technologies; The second is to implement more detailed environmental regulatory policies, including carbon emission standards, technical standards, and market access conditions; The third is to promote enterprises to realize low‐carbon transformation.